A velhice retratada nos filmes publicitários - Mazzaferro, Denise Salvador Morante (2013)
Statistics reveal that in 2050 Brazil will have more than 260 million, of which approximately 14 million will exceed the barrier of 80 years of age, materializing the phenomenon of longevity, agequake . Living in a consumer society, currently seniors travel, all around the world, visiting cities and museums, take computer courses, play sports, increasingly being the target of consumer markets. Today, the elderly Brazilians have a potential of consumption of R$ 7.5 billion, double of the national average. Considering that advertising, consumer and mass culture reflect and explain certain key features of modern-contemporary culture, this research aiming to show - in the current Brazilian socio-economic context - how advertising agencies and their clients portray the elderly public in their campaigns. Along these lines, 13 commercials that had the elderly as protagonists were selected as the focus of a critical analysis that investigated which concepts of elderliness were portrayed. The methodology chosen to develop this research was content analysis with the intent of, based on the identified cognitive units that compose the communication, transcend the reach of simply descriptive message, to reach a wider interpretation. Recurring themes were highlighted in the 13 films: - seven of them focused on the relationship between the elderly and technology; in three of them the elderliness was associated with memory, credibility, history and past - one, beauty or "no possibility of beauty" in old age, and two showed, the relationship between grandparents and grandchildren. The discussion of how these themes were used by advertisers and how they reinforce the stigmas and prejudices was the purpose of this research, presenting other possible representations of seniors and aging. It also points out where adjustments in communication are necessary in order to better portray aging, reinforcing it as one of the stages of life, with its unique features and full of possibilities